2022
DOI: 10.1002/cam4.5247
|View full text |Cite
|
Sign up to set email alerts
|

A pyroptosis‐related signature predicts prognosis and indicates immune microenvironment infiltration in glioma

Abstract: Background Glioma, the most common malignant brain tumor, leads to high recurrence rates and disabilities in patients. Pyroptosis is an inflammasomes‐induced programmed cell death in response to infection or chemotherapy. However, the role of pyroptosis in glioma has not yet been elucidated. Methods RNA‐seq data and clinical information of 660 gliomas and 847 samples were downloaded from the TCGA and CGGA, respectively. Then, data of 104 normal brain tissues was retrieved from the GTEx for differential express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…The performance of our prognostic model was compared with partially existing risk models using respective formulas in CGGA301 cohort (Supplementary Figure 5). AUCs and Cindex showed that our three-gene prognostic model achieved similarly great predictive performance compared with existing models (16)(17)(18). Despite the presence of higher accuracy in other models, their models contained more genes and lack of samples validation, which restricted the clinical applications (15,19).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The performance of our prognostic model was compared with partially existing risk models using respective formulas in CGGA301 cohort (Supplementary Figure 5). AUCs and Cindex showed that our three-gene prognostic model achieved similarly great predictive performance compared with existing models (16)(17)(18). Despite the presence of higher accuracy in other models, their models contained more genes and lack of samples validation, which restricted the clinical applications (15,19).…”
Section: Discussionmentioning
confidence: 93%
“…Currently, numerous prognostic models based on specific hallmark have been developed in glioma, but most of them contain more genes and lack of validation of clinical samples. Real clinical samples validation was usually confined in the level of gene expression, rather than the prognostic model, which actually do not have enough persuasion (15)(16)(17)(18)(19). In this study, we constructed a necroptosis-related prognostic model that comprised of three genes (EZH2, LEF1 and CASP1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And interestingly, the results indicated that glioma therapeutic response and immunosuppressive microenvironment are associated with high-risk scores. Previous studies have constructed multiple predictive signature to predict OS of gliomas, including aging-related genes signature [57] , chemokine-based signature [58] , and pyroptosis-related signature [59] . We compared the performance of these risk signatures with our FARGS using a previously reported method [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data also show that glioma patients expressing high level of pyroptosis-related genes(PRGs) have worse outcomes and are at greater risk of metastasis [37]. Moreover, compared to low-grade gliomas, high-grade gliomas have higher expression of PRGs probably associated with their malignant progression [38].…”
Section: Long-term Chronic Inflammation Modulates the Tmementioning
confidence: 99%